(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Nanotechnology, which is regarded as one of the major fields of global research, is currently generating more interest. We have worked in this direction for this aim. PP/α-Al2O3 composite samples were exposed to various levels of radiation in the article. The kinetics of changes are shown to be non-linearly dependent on the strength and quantity of the dose according to the findings of research carried out by other researchers. As a result of the effect of gamma radiation, various α-, α׳-, β-, δ-, etc. the change of molecular mobility of relaxation and structural elements. For the present period, it is very important to analyze the kinetics of the suggested processes of nanoscale fillers and the electret characteristics of polymer/nanocomposite systems following γ -irradiation. Considering the present importance of electret characteristics in practical applications for polymer/nanocomposite systems. The paper also discusses the lgρv = (T)dependences for PP/α-Al2O3 composite samples exposed to various levels of radiation. The dependences showed that the most thermally stable samples are those that have not been exposed to radiation. The temperature dependency of ρv became more acute when the radiation dose was increased to D = 80 kQr. As a result, load carriers in samples with PP/α-Al2O3 compositions are now more expensive.